2021
DOI: 10.1371/journal.pone.0251150
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of thermal screening in detection of COVID-19 among truck drivers at Mutukula Land Point of Entry, Uganda

Abstract: Introduction Despite the limited evidence for its effectiveness, thermal screening at points of entry has increasingly become a standard protocol in numerous parts of the globe in response to the COVID-19 pandemic. We sought to determine the effectiveness of thermal screening as a key step in diagnosing COVID-19 in a resource-limited setting. Materials and methods This was a retrospective cross-sectional study based on a review of body temperature and Xpert Xpress SARS CoV-2 test results records for truck dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Nsawotebba et al. 19 assessed the effectiveness of thermal screening in the detection of COVID-19 and reported a high specificity of 99.5%. Guan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nsawotebba et al. 19 assessed the effectiveness of thermal screening in the detection of COVID-19 and reported a high specificity of 99.5%. Guan et al.…”
Section: Discussionmentioning
confidence: 99%
“…The use of facemasks was encouraged in 42 hospitals and hand hygiene compliance was encouraged in 29 hospitals. Nsawotebba et al assessed the effectiveness of thermal screening for the detection of COVID-19 and reported a high specificity of 99.5% [ 23 ]. Guan et al reported that fever with a body temperature above 37.5°C occurs in 88% of COVID-19-positive patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This misconception can pose a health risk as not everyone with COVID-19 will have a high fever. A COVID-19 screening test is recommended in addition to thermal scanning (Nsawotebba et al, 2021). 65.6% of the respondents believe in the asymptomatic transmission of COVID-19.…”
Section: Discussionmentioning
confidence: 99%